Antimicrobial Use (AMU) in Polyculture Aquafarms of Mymensingh Sadar: Category, Quantity and Surveillance (Research in Agriculture Livestock and Fisheries, 2026)
Aquaculture has become one of the fastest-growing food production sectors, playing a critical role in nutritional security and rural livelihoods in Bangladesh. However, disease outbreaks in farming systems have increased reliance on antimicrobials, raising concerns about antimicrobial resistance (AMR) and environmental contamination. This study assessed the categories, quantity, and determinants of antimicrobial use (AMU) in polyculture aquafarms of Mymensingh Sadar Upazila (sub-district). The survey based study was conducted among 100 randomly selected polyculture fish farmers using a structured questionnaire. Data were collected on farm characteristics, antimicrobial types, dosage, duration, route of administration, and advisory sources. AMU was quantified using a weight-based method (mg/kg biomass), and statistical analyses including correlation and multiple regression, were performed to identify the influential factors. Findings revealed the widespread use of antibiotics, primarily for therapeutic purposes (91%), with fluoroquinolone group such as enrofloxacin, levofloxacin, and ciprofloxacin being the most frequently used agents. These drugs were classified as critically important for human medicine, heightening public health concerns. Most antimicrobials were administered as medicated feed, though a significant proportion was applied directly to pond water. Stocking density emerged as the strongest predictor of AMU, followed by pond size and farming experience. While withdrawal periods were commonly practiced, the provision of professional guidance was inconsistent, leading some farmers to depend on drug vendors or their own decisions. Overall, the study highlighted the urgent need for improved antimicrobial stewardship, farmer training, strengthened regulatory oversight, and systematic AMU surveillance to ensure sustainable aquaculture and mitigate the risk of antimicrobial resistance.Res. Agric. Livest. Fish. Vol. 13, No. 1, April 2026: 165-181